Applying a "fail‐fast" approach to conservation in US agriculture. Issue 3 (20th January 2022) - Wardropper, Chloe B.; Esman, Laura A.; Harden, Seth C.; Masuda, Yuta J.; Ranjan, Pranay; Weigel, Collin; Ferraro, Paul J.; Prokopy, Linda S.; Reddy, Sheila M. W.
Abstract: Conservation programs often operate for many years with little information on program performance or impacts. A better process would encourage programs to "fail fast"—in other words, to implement rapid testing to learn and adapt early, and thereby avoid wasting resources. Here, we present a fail‐fast approach applied in a multiyear field trial program that sought to improve soil health in the US Cornbelt on farmland owned by nonoperating landowners. While failing fast requires investment and a supportive team culture, we recommend that this approach to program design, with metrics tailored to the program context, be used early and frequently throughout planning and implementation phases to improve program processes and test assumptions well before final outcomes are detectable. Abstract : In this Perspective, we present our approach to conservation program design, which entails learning from small and frequent program failures and successes to evaluate innovative interventions before they are brought to scale. The fail‐fast approach is illustrated through a case study of a trial conservation program for rented farmland in the US Cornbelt.